A retrospective study of the influence of the vitreomacular interface on macular oedema secondary to retinal vein occlusion. Issue 10 (3rd March 2017) - Singh, Rishi P; Habbu, Karishma A; Bedi, Rumneek; Silva, Fabiana Q; Ehlers, Justis P; Schachat, Andrew P; Sears, Jonathan E; Srivastava, Sunil K; Kaiser, Peter K; Yuan, Alex
Abstract : Aims: To compare anti-vascular endothelial growth factor (VEGF) treatment outcomes for macular oedema (ME) secondary to retinal vein occlusion (RVO) based on vitreoretinal interface (VRI) status. Methods: This retrospective case series includes treatment-naive eyes diagnosed with RVO and treated with anti-VEGF injections. Eyes were stratified based on international VRI classification schema at baseline into three groups—vitreomacular traction (group A), no posterior vitreous detachment (PVD) (group B) and PVD without vitreomacular attachment (group C). Fifty-two eyes were identified based on inclusion/exclusion criteria. The primary endpoint was change in central subfield thickness (CST) on optical coherence tomography at 6 months. Results: There were no statistically significant differences in baseline characteristics of patients with RVO when stratified by VRI subgroups. After 6 months of treatment, there was no statistically significant difference in the change in CST from baseline between VRI cohorts (p=0.11). There was a trend demonstrating the greatest improvement in CST in eyes in group A compared with eyes in groups B and C (−224.13 μm, −160.88 μm and −50.92 μm, respectively, p=0.11 between cohorts). Mean change in logarithm of the minimum angle of resolution visual acuity from baseline to month 6 in group A compared with groups B and C was −0.25, −0.14 and −0.13, respectively (p=0.64 between cohorts). Conclusions: We did not identify an association between VRI status and treatment outcomes with anti-VEGF agents for ME secondary to RVO.